ANALISIS PERILAKU KONSUMEN TERHADAP KUALITAS LAYANAN BPS DI KABUPATEN MERAUKE PROVINSI PAPUA - Elsyan Rienette Marlisa (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
The Papua Provincial Government by placing BPS (Central Bureau of Statistics) as one of the assets that will be used to contribute services and data to the regional economy, as an institution that has the opportunity to become the leading contributor to contribute information about service quality aspects and data quality for the region through provision BPS data quality. This study aims to identify and analyze Asek Satisfaction and expectations for data user segmentation, BPS Service Quality and BPS data quality, level of satisfaction and provide recommendations on the type and quality of statistical data and information and analyze BPS Service Variables in Merauke Regency. The method used is Quantitative Analysis, Web Analysis and Cartesian Diagram (Importance Performance Analysis Matrix). The results of the study show that 1). The Value of Satisfaction and Expectation Aspects of Quality Service Aspects of BPS in Merauke Regency to date states that the value of aspects of satisfaction and expectation on data quality for satisfaction aspects states not to be satisfied with score 2.; The Value of Satisfaction and Expectation Aspects Against the Quality Aspect of BPS Data to date states that the Value of the Satisfaction Aspect Stating (Score 2) Not Satisfied and Expectations on BPS Service Quality Aspects Satisfaction states (Score 3) Is Important. 2) Attributes contained in Quadrant A are attributes 1. Requirements (2,915) and 5. Facilities (2,927) and 6. Complaint Services (2,927) that need to be considered by BPS to keep consumers satisfied with various BPSservices and BPS data quality . BPS Merauke Regency should make the factors contained in this quadrant A as a strategy to compete with other Data / Information Providers Institutions either conducted by Bappeda or NGOs and other institutions. Suggestion of findings: Provision of BPSServices needs to be improved so as to achieve minimum service standards, especially in terms of requirements must be reviewed and improve the Quality of HR involved in services by allocating operational costs